THE INFLUENCE OF KNOWLEDGE, SKILLS AND MOTIVATION ON INTEREST IN CREATIVE ECONOMIC ENTREPRENEURSHIP - Antoni, Syafrul; Karim, M (Politeknik Negeri Bengkalis, 2024)
abstact: This research aims to determine the influence of knowledge, skills and motivation on interest in creative economic entrepreneurship among students at the Faculty of Islamic Economics and Business (FEBI) ISLAMIC RELIGION INSTITUTE (IAIN) KERINCI. The type of research used in this research includes quantitative research with the help of a computer system. The sampling technique used in this research is random sampling, which is a technique used to determine a sample from a population that has certain characteristics up to the desired number (quota), namely 50 students. As many as 50 students of the Faculty of Islamic Economics and Business (FEBI) IAIN KERINCI completed the questionnaire in this research. Data analysis in this research used the SPSS version 26 programPartial findings show that knowledge does not have a significant and positive effect on interest in creative economy entrepreneurship among students of the Faculty of Islamic Economics and Business (FEBI) IAIN KERINCI, skills have a positive and significant effect on interest in creative economy entrepreneurship among students of the Faculty of Islamic Economics and Business (FEBI) IAIN KERINCI , motivation has no significant influence on interest in creative economy entrepreneurship among students at the Faculty of Islamic Economics and Business (FEBI) IAIN KERINCI. This shows that the better the knowledge, skills and motivation, the greater the interest in creative economic entrepreneurship among students at the Faculty of Islamic Economics and Business (FEBI) IAIN KERINCI.Â Keywords: Knowledge, Skills, Motivation, Creative Economy Entrepreneurial Interest.